PENGGUNAAN MEDIA POSTER DALAM LAYANAN BIMBINGAN BELAJAR KEGIATAN MBKM MAHASISWA UNIVERSITAS QUALITY PROGRAM KKN TEMATIK DESA SIJAMBUR KECAMATAN RONGGUR NIHUTA KABUPATEN SAMOSIR - Suciawati, Hasni; Tumanggor, Wasni Rosmawati (Universitas Quality, 2023)
Today, maybe everyone uses the media in carrying out activities, especially activities related to communication between one individual and another. One of them is learning media which is one of the methods or tools used in teaching and learning activities. This is done to stimulate learning patterns, support the success of the teaching and learning process, and enable teaching and learning activities to achieve their goals effectively. There are various types of learning media available. One of the challenges of learning media is to arouse students' interest in the learning material presented. One of the learning media used is poster media. Poster media is widely used in learning because it is simple and easy to make. Poster media is an illustration of a simplified image that aims to attract attention, be easy to remember and can understand the material being taught. Posters can be made using paper, computers, cardboard, and so on. Poster media can be said to be good if it meets certain criteria which include readability, visibility, legibility, and good composition. The purpose of this research is to develop the use of poster media in the learning process where posters have several functions, such as developing students' ideas and creativity, explaining a concept or process, describing objects and new vocabulary, as a tool to increase motivation, can explain a timeline, can convey messages and ideas, as well as inform an activity, agenda or specific schedule in the MBKM program tutoring at University of Quality KKN students in Sijambur Village, Kec. Roggur Nihuta Kab. Samosir and the method used is descriptive method.